Influence of TFAP2B and KCTD15 genetic variability on personality dimensions in anorexia and bulimia nervosa. Issue 9 (27th July 2017) - Gamero‐Villarroel, Carmen; González, Luz M.; Rodríguez‐López, Raquel; Albuquerque, David; Carrillo, Juan A.; García‐Herráiz, Angustias; Flores, Isalud; Gervasini, Guillermo
Abstract: Introduction: TFAP2B and KCTD15 are obesity‐related genes that interact to regulate feeding behavior. We hypothesize that variability in these loci, isolated or in combination, could also be related to the risk of eating disorders (ED) and/or associated psychological traits. Methods: We screened 425 participants (169 ED patients, 75 obese subjects, and 181 controls) for 10 clinically relevant and tag single‐nucleotide polymorphisms (SNPs) in KCTD15 and TFAP2B by the Sequenom MassARRAY platform and direct sequencing. Psychometric evaluation was performed with EDI‐2 and SCL‐90R inventories. Results: The KCTD15 rs287103 T variant allele was associated with increased risk of bulimia nervosa (BN) (OR = 4.34 [1.47–29.52]; p  = .003) and with scores of psychopathological scales of these patients. Haplotype *6 in KCTD15 was more frequent in controls (OR = 0.40 [0.20–0.80], p  = .009 for anorexia nervosa), while haplotype *4 in TFAP2B affected all three scales of the SCL‐90R inventory in BN patients ( p  ≤ .01). Epistasis analyses revealed relevant interactions with body mass index of BN patients ( p  < .001). Genetic profiles in obese patients did not significantly differ from those found in ED patients. Conclusions: This is the first study that evaluates the combined role of TFAP2B and KCTD15 genes in ED. Our preliminary findings suggest that the interaction of genetic variability in these loci could influence the risk for ED and/or anthropometric and psychological parameters. Abstract : TFAP2B and KCTD15 are obesity‐related genes that interact to regulate feeding behavior. In this paper, we show that genetic variants in these genes can also interact to influence the risk of eating disorders and/or associated personality dimensions.